Aesthetic affordances: Computer animation and Wayang Kulit puppet theatre. Issue 1 (1st December 2013) - Jernigan, Daniel K.; Chansavang, Anthony; Martin-Rall, Hannes; Hock-Soon, Seah; Lim, Darren; Johan, Henry
This article describes the various animation techniques we used in creating our short animated piece, Si Lunchai (based on the Indonesian folktale of the same name). We took our aesthetic inspiration from Indonesian Shadow Puppetry (Wayang Kulit). Because 3D animation technology provides many 'naturalistic' advantages not available in traditional shadow puppet performances, much of the challenge of the work involved seeking out compelling compromises between retaining the aesthetic value of the original Wayang Kulit, while also taking advantage of the various affordances of 3D animation. Among other things, this essay describes working with 2D characters in a layered (2.5-D) environment, character mobility and pivot points, character 'flipping' and our attempt to maintain some sense of the live action quality of Wayang Kulit theatre.